2020
DOI: 10.1155/2020/8830471
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circulating RBP4 in the Type 2 Diabetes Patients with Kidney Diseases: A Systematic Review and Meta-Analysis

Abstract: Background. Diabetic nephropathy is a common and serious complication of diabetes mellitus (DM) and is one of the leading causes of end-stage renal disease worldwide. Although there have been many investigations on biomarkers for DN, there is no consistent conclusion about reliable biomarkers. The purpose of this study was to perform a systematic review and meta-analysis of the role of circulating retinol-binding protein 4 (RBP4) in the type 2 diabetes mellitus (T2DM) patients with kidney diseases. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
(90 reference statements)
0
22
1
Order By: Relevance
“…e concentration of Cys C in the blood is determined only by the glomerular filtration rate and is not affected by physiological and pathological factors such as age and inflammation, so it can be used as a sensitive indicator to assess glomerular and tubular lesions [14,15]. As an indicator that can also reflect the function of glomeruli and tubules, RBP4 is getting more and more attention in clinical practice, and it was mainly used as a screening marker for diabetic nephropathy and attracted attention in the early stage [16]. RBP4 is mainly synthesized by hepatocytes and is produced at a constant rate, and most of it can be reabsorbed by the Evidence-Based Complementary and Alternative Medicine renal tubules after passing through the glomerular filtration membrane, so the concentration of RBP4 in the blood is less affected by other factors when it is under normal physiological conditions [17].…”
Section: Discussionmentioning
confidence: 99%
“…e concentration of Cys C in the blood is determined only by the glomerular filtration rate and is not affected by physiological and pathological factors such as age and inflammation, so it can be used as a sensitive indicator to assess glomerular and tubular lesions [14,15]. As an indicator that can also reflect the function of glomeruli and tubules, RBP4 is getting more and more attention in clinical practice, and it was mainly used as a screening marker for diabetic nephropathy and attracted attention in the early stage [16]. RBP4 is mainly synthesized by hepatocytes and is produced at a constant rate, and most of it can be reabsorbed by the Evidence-Based Complementary and Alternative Medicine renal tubules after passing through the glomerular filtration membrane, so the concentration of RBP4 in the blood is less affected by other factors when it is under normal physiological conditions [17].…”
Section: Discussionmentioning
confidence: 99%
“…RBP4 is associated with cardiovascular risk in type 2 diabetic subjects with varying clinical presentations [32]. Recent studies demonstrated that RBP4 levels significantly alter with variables related to insulin resistance, obesity, type 2 diabetes and metabolic syndrome [32][33][34]. Furthermore, there is some indication that reduced RBP4 levels decrease the risk of diabetic nephropathy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that RBP4 levels significantly alter with variables related to insulin resistance, obesity, type 2 diabetes and metabolic syndrome [32][33][34]. Furthermore, there is some indication that reduced RBP4 levels decrease the risk of diabetic nephropathy [34]. The plasma level of RBP4 is higher in type 2 diabetic patients when compared with normal controls [35].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of proteins [38], metabolism [39], the citric acid (TCA) cycle and respiratory electron transport [40], gluconeogenesis [41], immune system [42], heterocyclic compound binding [43], protein binding [44], establishment of localization [45], cellular metabolic process [46], cytoplasm [47] and catalytic activity [48] were the GO terms and signaling pathways responsible for the advancement of T2DM. A previous study showed that IGFBP2 [88], CPT1A [89], ALDH1B1 [90], ESRRA (estrogen related receptor alpha) [91], NISCH (nischarin) [92], SSTR3 [93], ND1 [94], NCOR2 [95], RBP4 [96], GSTP1 [97], CYB5A [98], G6PC2 [99], DNAJC15 [100], TMED6 [101], PSMD6 [102], CLU (clusterin) [103], TTR (transthyretin) [104], TXN (thioredoxin) [105], LAMTOR1 [106], GLUL (glutamate-ammonia ligase) [107], NEU1 [108], HSPA8 [109], AP3S2 [110], COX4I1 [111], MT2A [112] MTCH2 [113], ESD (esterase D) [114], UBE2L6 [115], SCD (stearoyl-CoA desaturase) [116], MGST3 [117] [187], GRB2 [188], ZMPSTE24 [189], COX6B1 [190], SQSTM1…”
Section: Discussionmentioning
confidence: 99%